Modulation of the Spin State of Atomic Fe-N4 Sites with Interlayer-Adjacent Ir-N4 for Superior ORR Activity - Tan, Yan; Li, Aoshuang; Wang, Yijie; Jiang, Xiucai; Cheng, Yiwen; Chao, Dongliang; Zhang, Yuzhong; Cheng, Chuanwei (Nano-Micro Letters, 2026)
Development of efficient and durable oxygen reduction reaction (ORR) electrocatalysts is of great interest yet remains challenging. Herein, we predicted and screened a bilayer graphite carbon-supported Ir-N4/Fe-N4 catalyst with high ORR activity using density functional theory calculations. Subsequently, various bimetallic single atom supported on 3D ordered macroporous carbon were rationally designed and experimentally synthesized via a colloidal microsphere template-confined reaction method. As anticipated, the resulting Ir-N4/Fe-N4 bimetallic single-atom catalysts (IrFe-SACs) exhibit superior ORR activity and durability, reaching a half-wave potential of 0.928 V. The IrFe-SACs also demonstrate outstanding performance in Zn-air batteries, including a high discharge power density (314 mW cm⁻2) and excellent cycling stability ( 1650 cycles over 550 h). Further experimental characterizations and theoretical analysis reveal that introducing interlayer-adjacent Ir-N4 sites facilitates the transition of Fe-N4 from a low-spin state to a medium-spin state, which optimizes the spin polarization of Fe 3d orbitals and enhances the non-localization of the Fe–O/OH molecular orbital, thereby significantly improving the ORR intrinsic activity and durability of atomic Fe-N4 sites. Highlights: 1 Ir-N4 induce spin polarization and trigger a low-spin to medium-spin transition at Fe centers, enhancing electron delocalization in Fe-O frontier orbitals, optimizes oxygen intermediate adsorption energies. 2 Modulation of spin state of active center optimizes the adsorption energy and enhancing intrinsic catalytic activity (E1/2 = 0.928 V for oxygen reduction reaction). 3 3D ordered macroporous carbon framework ensures high accessibility of atomic sites, resulting in excellent batteries performance, i.e., a discharge power density of 314 mW cm−2, specific capacity of 817.5 mAh g−1.